Time-dependent behavior of rock-like specimen containing multiple discontinuous joints under uniaxial step-loading compression. (June 2021) - Yang, Wendong; Bo, Chunjie; Chen, Xuguang; Huang, Chenchen; Li, Guizhi
Rock with multiple discontinuous joints widely exists in rock engineering, and its mechanical properties are complex, which greatly increases the difficulty of engineering design and construction. Time-dependent deformation characteristics and long-term strength evaluation of jointed rock masses remain poorly understood. In this work, the creep experiments of rock-like specimens with multiple discontinuous joints under uniaxial step-loading compression are carried out to explore the influence of joint geometry (rock bridge length, joint length, joint angle, and joint spacing) on creep strain, long-term strength, and failure pattern of specimens with multiple discontinuous joints. The following conclusions are drawn from the test results: 1) The deformation of jointed rock specimens has evident time-dependent effect, and the cumulative creep deformation increases as creep load increases; 2) The strength of jointed rock specimens under loading changes with time, and the ratio of long-term strength and creep peak strength ( σ ∞ / σ c ) of the tested specimens ranges from 41% to 96%; 3) The distribution of initial joints affects the creep fracture modes of rock-like specimens. The rupture of rock-like specimens with different joints distribution is mainly caused by the growth of wing cracks and quasi-coplanar secondary cracks. Three different failure modes are observed from these specimens: i) tensile failure with cracks across the joint plane; ii) shear failure with cracks along the joint plane; and iii) tensile failure with cracks along the joint plane. Based on the principles of damage mechanics and fracture mechanics, a theoretical mechanistic model considering both the closure stage of pre-existing open joints and time-dependent propagation stage of new cracks is established. Considering the influence of joint length, joint angle and joint density, the evolution of creep strain of rock-like specimen with multiple discontinuous joints is analyzed. The theoretical model results agree well with the experimental results, which indicates that the established model can replicate the creep failure process of jointed rock mass. These theoretical and test results help us better understand the effect of multiple joints on the long-term behavior of rock mass.